A Case of Successful Pregnancy in a Ewe with Uterus Didelphys. Issue 5 (18th June 2013) - Carr, DJ; Aitken, RP; Milne, JS; David, AL; Wallace, JM
Contents: Uterus didelphys is a rare congenital abnormality of the reproductive tract. Although it occurs in various species, there are no published reports describing pregnancy outcome in association with this abnormality. Herein we describe a case of successful unilateral singleton pregnancy in a ewe incidentally found to have uterus didelphys during the course of a biomedical research study. The pregnancy was established using assisted reproductive techniques and interrupted in late gestation, at which point the abnormality was identified. Serial ultrasound assessment of foetal biometry revealed a normal foetal growth trajectory. Despite a 45% reduction in placentome number, total placentome weight was near normal secondary to compensatory placentome growth and development. To our knowledge, this is the first detailed report of normal foetal growth in an animal with uterus didelphys and illustrates the ability of the ovine placenta to adapt to a reduced number of placentomes and maintain foetal nutrient supply.